Electron beam and gamma irradiation as feasible conservation technologies for wild Arenaria montana L.: Effects on chemical and antioxidant parameters. (August 2016) - Pereira, Eliana; Barros, Lillian; Barreira, João C.M.; Carvalho, Ana Maria; Antonio, Amilcar L.; Ferreira, Isabel C.F.R.
Abstract: Wild plants are widely recognized as high-potential sources of several bioactive compounds. Nevertheless, these natural matrices require effective decontamination steps before they might be considered for different industrial purposes. Irradiation techniques are being progressively acknowledged as feasible conservation methodologies, either for their high decontamination effectiveness, as well as for their innocuousness on most chemical and bioactive parameters of the material to be treated. Arenaria montana L. (Caryophyllaceae) is recognized for its phytochemical richness, having a relevant geographical distribution in the Southern Europe. Herein the effects of irradiation (gamma and electron beam up to 10 kGy) were evaluated by comparing the nutritional, chemical and antioxidant profiles in A. montana extracts. In general, the assayed parameters showed statistically significant variations in response to irradiation treatment. Furthermore, the performed LDA allowed identifying the antioxidant indicators as the most affected parameters in irradiated samples, especially when using the 10 kGy dose and e-beam irradiation. Industrial relevance: Wild plants are recognized as high-potential sources of several bioactive compounds. Nevertheless, they require effective decontamination steps before being considered for different industrial purposes. Irradiation techniques are being progressively acknowledged as feasible decontamination methodologies, but several options are available. The present study, using Arenaria montana as a case-study, reports important clues for choosing a specific irradiation type or dose according to the need of maintain a specific chemical or bioactive profile. Highlights: Most of the characterized parameters showed statistically significant variations. E-beam irradiation showed a general tendency to increase antioxidant activity. Antioxidant parameters suffered the most significant changes with 10 kGy and e-beam.